Interconnected collagen porous scaffolds prepared with sacrificial PLGA sponge templates for cartilage tissue engineering. Issue 40 (23rd September 2021) - Xie, Yan; Lee, Kyubae; Wang, Xiuhui; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract : Interconnected collagen porous scaffolds were prepared using PLGA sponges as sacrificial templates and applied for cartilage tissue engineering. Abstract : Interconnected pore structures of scaffolds are important to control the cell functions for cartilage tissue engineering. In this study, collagen scaffolds with interconnected pore structures were prepared using poly(d, l -lactide- co -glycolide) (PLGA) sponges as sacrificial templates. Six types of PLGA sponges of different pore sizes and porosities were prepared by the solvent casting/particulate leaching method and used to regulate the interconnectivity of the collagen scaffolds. The integral and continuous templating structure of PLGA sponges generated well-interconnected pore structures in the collagen scaffolds. Bovine articular chondrocytes cultured in collagen scaffolds showed homogenous distribution, fast proliferation, high expression of cartilaginous genes and high secretion of cartilaginous extracellular matrix. In particular, the collagen scaffold templated by the PLGA sacrificial sponge that was prepared with a high weight ratio of PLGA and large salt particulates showed the most promotive effect on cartilage tissue formation. The interconnected pore structure facilitated cell distribution, cell–cell interaction and cartilage tissue regeneration.